Two novel InDels within the promoter of SIRT1 are associated with growth traits in chickens. Issue 4 (4th July 2022) - Liu, D.; Liu, X.; Ma, X.; Li, C.; Li, J.; Li, Q.; Zhang, N.; Cao, Y.; Li, Z.; Kang, X.; Tian, Y.; Li, W.
ABSTRACT: 1. The objectives of the present study were to elucidate the relationship between novel variations of the SIRT1 gene and chicken growth traits. In total, 1, 429 chickens, including six breeds and a Gushi ×Anka F2 resource population, were genotyped using PCR-RFLP. 2. Two novel InDels (c.-1552_-1553insCG and c.-450_-451delCG) in the promoter of the chicken SIRT1 gene were identified. An association study showed that c.-1552_-1553insCG was significantly correlated with growth traits and serum lipid indicators. 3. The insertion genotype was most highly associated with body weight at day old, two- and four-week-old chickens, and with shank circumference at four and eight weeks of age. The wild type genotype at this site was most highly associated with serum lipid indicators. 4. In contrast, c.-450_-451delCG was significantly correlated with muscle fibre diameter. The SIRT1 gene expression in chickens with different InDel genotypes was analysed and was significantly higher with heterozygous genotypes at both sites in muscle and fat tissue, relative to expression in chickens with the corresponding homozygous genotypes. 5. The effects of different haplotypes on SIRT1 promoter activity showed that promoter activity depends on haplotype, with haplotype HapII exhibiting the highest activity. 6. It was concluded that the SIRT1 gene is associated with chicken growth traits and that the two InDels influence SIRT1 promoter activity in chickens.